Pengembangan Bahan Ajar Bahasa Indonesia Sekolah Dasar Berbasis Strategi Belajar Bahasa - - Dawud (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Strategy of language learning can be seen as a general or a special action that is done by language learner for solving problems in language learning or non language learning. Based on information processing model in language learning, language learning strategy can be divided to cognitive strategy, meta cognitive strategy, and social strategy. Learning material development of Indonesia language in the elementary school should consider language learning that is used by language-learner so the learning material can be appropriate to learning mechanism. The appropriateness learning material and learning strategy can facilitate and accelerate language learning.